Strategic management and demarketing in UNESCO WHSs: a comparative analysis of two Croatian tourist destinations - Krajnović Aleksandra; Raguz Ivona Vrdoljak; Gortan-Carlin Ivana Paula (Bulletin of Geography. Socio-Economic Series)
This paper studies the protected cultural property strategic management conducted by UNESCO, the World Heritage Sites (WHS). Its purpose is to explore the measure to which the system of such cultural property management is developed, since its meaning goes beyond the touristic purpose and indicates the world’s cultural property. Two Croatian tourist destinations are examined – Dubrovnik and Poreč. At the end of the paper, a comparative analysis of the two investigated cases is presented with the aim of presenting the research results and designing a personal model and conceptual frame of action to create a more efficient management system for protected heritage at all levels